(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The study was undertaken to determine the purity level of eleven selected pesticides collected from different locations of Bangladesh. In this study, Gas Chromatography coupled with Flame Ionization Detector (FID) and Electron Captured Detector (ECD) was used to determine the purity of acephate, diazinon, dimethoate, chlorpyrifos, quinalphos, malathion, fenitrothion cypermethrin, fenvalerate. High Performance Liquid Chromatography (HPLC 20A Prominence) coupled with Photo Diode Array (PDA) detector was used to determine the purity of carbofuran and carbosulfan. Results indicated that 40% of the tested pesticides have lower active ingredient (ai) than stated on the label of container. A total of 11 pesticides were tested. The purity of all tested brands of fenvalerate and fenitrothion were 100%. The purity of cypermethrin ranged from 72-100%. The purity of organocarbamate pesticide carbofuran and carbosulfan ranged from 70-100% and 95-100%, respectively. The purity of dimethoate, chlorpyrifos, malathion, quinalphos, diazinon and acephate ranged from 63-100%, 67-100%, 79-100%, 83-100% and 68-100%, respectively. Bangladesh J. Agril. Res. 46(2): 167-174, June 2021